Suboptimal Antiretroviral Drug Levels and Virologic Failures among PLHIV at a Rural Referral Hospital in South Western Uganda: A Descriptive Crosssectional Study. - Twinomujuni, Silvano Samba; Ogwang, Patrick E.; Roelofsen, Felicitas; Mukonzo, Jackson K.; Atukunda, Esther Cathyln (Research square, 2020)
Background: Achieving favorable HIV treatment outcomes is a major challenge, particularly due to non-adherence and consequent sub-therapeutic plasma antiretroviral drug levels. This is often complicated by the development of resistant strains due to mutations. Monitoring antiretroviral drug levels in the blood of patients enrolled on ART can reveal if levels are too high, enough, or too low. High levels may lead to dose-dependent side effects and sub-therapeutic levels could promote treatment failure and resistance. In Uganda, as part of routine HIV care, plasma antiretroviral drug level is estimated indirectly by clinic-based pill counts and patient self-reported adherence, which give no evidence of ingested medication. This study aimed at exploring steady state nevirapine and efavirenz drug levels in HIV patients accessing ART at a rural referral hospital in South Western Uganda. Methods: This study was nested into a randomized clinical trial that evaluated the effect of Artemisia annua L. and Moringa oleifera on immunological response and viral load among persons living with HIV (PLHIV). In the parent study, 250 HIV-infected patients with continued immunologic suppression (CD4 count < 350cells/μL) despite a minimum of one-year on ART were enrolled. Out of 250 clinical trial participants, 95 were randomly selected for steady-state efavirenz and nevirapine plasma concentration sampling having taken the last at bedtime. Additionally, CD4 count, HIV load, liver, and renal function tests were determined. Participants were also interviewed for adherence, and factors that affect blood drug levels. Results: Of the 95 participants sampled, 67 (71%) and 28 (30%) were on efavirenz or nevirapine based ART respectively. The median viral load for participants on the efavirenz regimen was 490 copies/mL (IQR 116, 1900) while that for the participants on the nevirapine regimen was 500 copies/mL (IQR 137, 1270). The median plasma level for the participants on the nevirapine regimen (6.56 mg/L IQR 4.50, 9.80) was higher than that for the participants on the efavirenz regiment (2.54 mg/L IQR 1.47, 5.12). The prevalence of virologic failure among participants sampled on the efavirenz regimen was higher (37%) compared to that of the participants on the nevirapine regimen (21%). 30% of all plasma samples tested had sub-therapeutic levels of either efavirenz or nevirapine, including 2% in which no drugs were detected. Conclusion: Periodic therapeutic drug monitoring should be incorporated as one of the components in the monitoring of ART adherence to ensure adequate blood levels among adults accessing ART at MRRH, SW Uganda.
Keywords: Antiretroviral Drug Levels; Efavirenz; Nevirapine; Virologic Failures; Uganda